An Important Role of the SDF-1/CXCR4 Axis in Chronic Skin Inflammation - Zgraggen, Silvana; Huggenberger, Reto; Kerl, Katrin; Detmar, Michael (PloS one, 2014)
Inflammatory angiogenesis and vascular remodeling play key roles in the chronic inflammatory skin disease psoriasis, but little is known about the molecular mediators of vascular activation. Based on the reported elevated mRNA levels of the angiogenic chemokine stromal cell-derived factor-1 (SDF-1) and its receptor CXCR4 in psoriasis, we investigated the relevance of the SDF-1/CXCR4 axis in two experimental models of chronic psoriasis-like skin inflammation. The cutaneous expression of both SDF-1 and CXCR4 was upregulated in the inflamed skin of K14-VEGF-A transgenic mice and in imiquimod-induced skin inflammation, with expression of CXCR4 by blood vessels and macrophages. Treatment with the CXCR4 antagonist AMD3100 potently inhibited skin inflammation in both models, associated with reduced inflammatory angiogenesis and inflammatory cell accumulation, including dermal CD4+ cells and intraepidermal CD8+ T cells. Similar anti-inflammatory effects were seen after treatment with a neutralizing anti-SDF-1 antibody. In vitro, inhibition of CXCR4 blocked SDF-1-induced chemotaxis of CD11b+ splenocytes, in agreement with the reduced number of macrophages after in vivo CXCR4 blockade. Our results reveal an important role of the SDF-1/CXCR4 axis in skin inflammation and inflammatory angiogenesis, and they indicate that inhibition of the SDF-1/CXCR4 axis might serve as a novel therapeutic strategy for chronic inflammatory skin diseases.